2012
DOI: 10.1073/pnas.1214415110
|View full text |Cite
|
Sign up to set email alerts
|

Topological specificity and hierarchical network of the circadian calcium rhythm in the suprachiasmatic nucleus

Abstract: The circadian pacemaker in the hypothalamic suprachiasmatic nucleus (SCN) is a hierarchical multioscillator system in which neuronal networks play crucial roles in expressing coherent rhythms in physiology and behavior. However, our understanding of the neuronal network is still incomplete. Intracellular calcium mediates the input signals, such as phase-resetting stimuli, to the core molecular loop involving clock genes for circadian rhythm generation and the output signals from the loop to various cellular fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
116
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(130 citation statements)
references
References 42 publications
14
116
0
Order By: Relevance
“…First observed in ex vivo brain sections (Hastings et al 1999;Koinuma et al 2013), the wave can also be observed with exquisite precision in organotypic slices (Yamaguchi et al 2003;Maywood et al 2013). The transcriptional rhythm is also associated with, and likely synchronized by, a circadian wave of [Ca 2þ ] i (Enoki et al 2012;Brancaccio et al 2013). As with CRE-dependent transcriptional rhythms, the [Ca 2þ ] i wave is suppressed by TTX and coherence between dorsal and ventral compartments is progressively lost.…”
Section: Intrinsic Mechanisms Of Synchronizationmentioning
confidence: 85%
See 1 more Smart Citation
“…First observed in ex vivo brain sections (Hastings et al 1999;Koinuma et al 2013), the wave can also be observed with exquisite precision in organotypic slices (Yamaguchi et al 2003;Maywood et al 2013). The transcriptional rhythm is also associated with, and likely synchronized by, a circadian wave of [Ca 2þ ] i (Enoki et al 2012;Brancaccio et al 2013). As with CRE-dependent transcriptional rhythms, the [Ca 2þ ] i wave is suppressed by TTX and coherence between dorsal and ventral compartments is progressively lost.…”
Section: Intrinsic Mechanisms Of Synchronizationmentioning
confidence: 85%
“…Moreover, although this rhythm was initially thought to be independent of action potential firing and reach its maximum about 4 h in advance of peak electrical activity (Ikeda et al 2003), more recent analysis using genetically encoded reporters indicates simultaneous peaks of cytosolic [Ca 2þ ] i and electrical activity. Furthermore, the cytosolic [Ca 2þ ] i rhythm is abrogated when action potentials are blocked by TTX (Enoki et al 2012;Brancaccio et al 2013), as observed in Per gene expression. The regulatory elements of Per1 and Per2 contain calcium-response elements (CREs) that may mediate the effect of the [Ca 2þ ] i rhythm on Per transcription (Travnickova-Bendova et al 2002), and indeed CRE-dependent gene expression (as reported by a CRE-luciferase viral construct) shows a pronounced circadian cycle that peaks after the daily surge in [Ca 2þ ] i and before peak Per1 expression (Brancaccio et al 2013).…”
Section: Controlling the Molecular Clockworkmentioning
confidence: 86%
“…Former data showed that Ca 2+ mobilized from internal deposits modulates the molecular circadian clock of hepatic cells ex vivo, in a manner that did not depend on the entrainment cue (meal or light) [4]. This suggests that Ca 2+ signaling is a key regulator of circadian rhythms in peripheral tissues in contrast to the central pacemaker mediating hierarchical organization of rhythmicity [25].…”
Section: Discussionmentioning
confidence: 99%
“…Calcium mediates intracellular clock signals, such as entrainment processes [6,23,30], clock gene expression [33,37,45,55], and output signaling [2]. Moreover a topological specificity of the circadian Ca 2+ rhythm in SCN was observed, suggesting that calcium plays a role in the hierarchical organization of rhythmicity in the central pacemaker [25].…”
Section: Introductionmentioning
confidence: 99%
“…But what initiates and drives all the action between SCN, neuronal networks, neurotransmitter release to cellular functions and coordinate their work at the intracellular level, are calcium ions (Ca2+), because once they enter the cytosol, they exert different effects on proteins and coordinates numerous cell functions (Enoki et al, 2017). The research done by shutting down the input pathway by tetrodotoxin (TTX) reduces the amplitude of Ca2+ rhythms by approximately 30%, assuming that intracellular Ca2+ levels are managed by both input pathways to the core loop and output pathways from the loop to diverse cellular functions (Enoki et al, 2012). All this indicates not only the importance of the role of calcium ions, but also the synchronization and correlation of all these components because disruption of one factor destabilizes the entire system.…”
Section: Mechanisms Of Molecular Backgroundmentioning
confidence: 99%